Ответ:
1.1)-3.4*2,7=-9,18
[tex] -1 \frac{3}{11} \times ( - 2 \frac{2}{21} ) = \frac{8}{33} [/tex]
3)-12,72:(-0,4)=31,8
4)15,45:(-15)=-1,03
2.1)-1,5а*(-6b)=9ab
2)-4m-15n+3m+18n=3n-m
3)b+(7-b)-(14-b)=b+7-b-14+b=b-7
4)-2(x-3)+4(x+1)=-2x+6+4x+1=2x+7
3. (-1,14-0,96):(-4,2)+1,8*(-0,3)=-2,1:(-4,2)+(-0,54)=0,5+(-0,54)=-0,04
4. - 3(1,2x-2)-(4-4,6x)+6(0,2x-1)= -3,6x+6-4+4,6x+1,2x-6=2,2x-4
[tex] - \frac{15}{22} \times 2.2 - 4 = - \frac{11}{2} = - 5.5 [/tex]
5. 0,9x-(0,7x+0,6y)=0,9x-0,7x-0,6y=0,2x-0,6y |*5
x-3y |*-1
3y-x=9
Ответ:9
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1.1)-3.4*2,7=-9,18
[tex] -1 \frac{3}{11} \times ( - 2 \frac{2}{21} ) = \frac{8}{33} [/tex]
3)-12,72:(-0,4)=31,8
4)15,45:(-15)=-1,03
2.1)-1,5а*(-6b)=9ab
2)-4m-15n+3m+18n=3n-m
3)b+(7-b)-(14-b)=b+7-b-14+b=b-7
4)-2(x-3)+4(x+1)=-2x+6+4x+1=2x+7
3. (-1,14-0,96):(-4,2)+1,8*(-0,3)=-2,1:(-4,2)+(-0,54)=0,5+(-0,54)=-0,04
4. - 3(1,2x-2)-(4-4,6x)+6(0,2x-1)= -3,6x+6-4+4,6x+1,2x-6=2,2x-4
[tex] - \frac{15}{22} \times 2.2 - 4 = - \frac{11}{2} = - 5.5 [/tex]
5. 0,9x-(0,7x+0,6y)=0,9x-0,7x-0,6y=0,2x-0,6y |*5
x-3y |*-1
3y-x=9
Ответ:9